The Implementation of Sustainable Development Goals (SDGs) Indicators at Makassar International Eight Festival & Forum 2023 by PT Festival Delapan Indonesia - Rizky Ady Satria Mulya; Firman Karim, Muhammad; Syafruddin (Journal of Event, Travel and Tour Management, 2024)
Sustainable Event are currently being echoed at this time, especially with the statement that events that produce negative impacts cannot be continued. One of the events that concern for the environment is Makassar International Eight Festival & Forum 2023. This research aims, To assess the extent to which the concept of sustainable event management has been implemented. The sustainability indicators used in this research are guided by the Sustainable Development Goals (SDGs) which have 17 global goals including, No Poverty, Zero Hunger, Good Health and Well-Being , Quality Education, Gender Equality, Clean Water and Sanitation, Affordable and Clean Energy, Decent Work and Economic Growth, Industry, Innovation and Infrastructure, Reduced Inequalities, Sustainable Cities, and Communities, Responsible Consumption and Production, Climate Action, Life Below Water, Life on Land, Peace, Justice and Strong Institutions, Partnership For the Goals. In this research the author used qualitative research methods. The data collection techniques in this research are interviews, document analysis and documentation. Informants in the research consisted of the main director and visitors to the Makassar International Eight Festival & Forum 2023. The results of this research show that there is one global goal of the Sustainable Development Goals (SDGs), namely SDGs 2 Zero Hunger, which has not been implemented. The 16 global SDGs goals have been implemented. Apart from that, the efforts made by the organizers also need to be increased to support sustainable events. Key Words : Festival, Sustainable Development Goals;Sustainable Event;Management ;Sustainability